Sarawak State Election 2016 : a survey on Chinese voter behaviour in Padungan (N9) / Chai Shin Yi, Nur Afisha Yusuf and Yong Sze Wei - Shin Yi, Chai; Yusuf, Nur Afisha; Sze Wei, Yong (Universiti Teknologi MARA, Shah Alam, 2016)
This paper examines the behaviour of Chinese voters in N9 Padungan during the recent 2016 Sarawak State Election. As an urban constituency with 92.8% Chinese voters, the BN has been trying to attract back the voters since it lost the seat to the opposition in 2006. Several reasons have been documented for this lost, including the failure of the SUPP to fight for the rights of the Chinese and issues on corruption as well as high cost of living. Under the new chief minister Adenan Satem, the BN has managed to attract support of the Chinese by reclaiming the 6 seats lost in 2011. However, the opposition still maintained its dominance in the N9 Padungan seat. Therefore, this study intended to identify the factors that influences the Chinese voters in their choice of candidates and reasons why the opposition is popular in this seat. Questionnaires were distributed and informal interviews conducted during campaigning period, targeting voters in the N9 Padungan constituency. The findings of this survey identified several factors such as retro